The Role of Glutamate Receptors in Epilepsy - Tsang-Shan Chen; Tzu-Hsin Huang; Ming-Chi Lai; Chin-Wei Huang (Biomedicines, 2023)
Glutamate is an essential excitatory neurotransmitter in the central nervous system, playing an indispensable role in neuronal development and memory formation. The dysregulation of glutamate receptors and the glutamatergic system is involved in numerous neurological and psychiatric disorders, especially epilepsy. There are two main classes of glutamate receptor, namely ionotropic and metabotropic (mGluRs) receptors. The former stimulate fast excitatory neurotransmission, are N-methyl-d-aspartate (NMDA), α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA), and kainate; while the latter are G-protein-coupled receptors that mediate glutamatergic activity via intracellular messenger systems. Glutamate, glutamate receptors, and regulation of astrocytes are significantly involved in the pathogenesis of acute seizure and chronic epilepsy. Some glutamate receptor antagonists have been shown to be effective for the treatment of epilepsy, and research and clinical trials are ongoing.